The Impact of Bank Ownership Structure on Green Banking Practices in Indonesia: The Moderating Role of Corporate Governance - Kartiko, Nafis Dwi; Firmansyah, Amrie (The International Journal of Financial Systems, 2024)
This study aims to analyze the impact of institutional, foreign, and government ownership on green banking disclosure in Indonesia. The sample includes 578 observations of banking companies in Indonesia over the period 2004 to 2021, and is analyzed using the OLS multiple linear regression method. The findings show that institutional and foreign ownership are negatively correlated with green banking disclosure, while government ownership has no significant impact. In terms of corporate governance moderation, this study shows that governance strengthens the positive effect between institutional ownership and green banking disclosure, but weakens the relationship between foreign ownership and green banking disclosure.